1126 SPINDLE ACTIVITY RELATED TO MOTOR PROCEDURAL LEARNING IN PATIENTS WITH SCHIZOPHRENIA. (28th April 2017) - Mylonas, DS; Demanuele, C; Baran, B; Kohnke, EJ; Tocci, C; Stickgold, R; Hamalainen, M; Manoach, DS
Abstract: Introduction: (EEG) oscillation characteristic of stage 2 non-rapid eye movement sleep (N2), mediate sleep-dependent memory consolidation. Patients with schizophrenia (SZ) have reduced sleep spindle density (spindles per minute) during N2 and a correlated deficit in sleep-dependent motor procedural memory. In this study we examined whether motor learning leads to regionally specific spindle increases in the motor network in the nap that follows learning, whether local spindle increases correlate with post-nap performance improvement and whether SZ patients differ from controls in spindle changes and memory improvement. Methods: SZ patients (n=15) and demographically-matched healthy controls (HC, n=12) were trained on the finger tapping motor sequence task (MST) and their performance tested after a 90 minute nap opportunity. We acquired continuous EEG and magnetoencephalographic (MEG) data simultaneously during MST training, the nap and MST testing. We computed the motor evoked responses, time-locked to each finger tap, for each subject during MST training and derived the anatomical constrained current source estimates using the minimum norm estimation method on both the EEG and MEG data. Results: Preliminary analysis of 4 HC and 4 SZ patients showed that the subjects had sufficient sleep time (63.9 ± 22.7 min) during MEG. Both groups showed significant overnap performance improvement on MST and did not differ in this regard. The SZ group exhibited reduced spindle density over the central and frontal electrodes. This spindle density deficit was also prominent at the MEG sensors. The source localization of the motor evoked responses revealed right lateralized activation of the primary and supplementary motor areas for both groups. Conclusion: These preliminary findings demonstrate the use of MEG/EEG to localize cortical sources of motor performance. We are presently conducting analyses to test our hypothesis that motor learning leads to specific spindle increases in the motor network that correlate with sleep-dependent memory consolidation in HC but not in SZ patients Support (If Any): This research was supported by K24 MH099421 (DSM) and Vergottis Postdoctoral Fellowship (DM)